Disparity in attitudes regarding assisted dying among physicians and the general public in Japan - Yoshiyuki Takimoto; Tadanori Nabeshima (BMC Medical Ethics)
Abstract Background Recently, an increasing number of countries have been allowing voluntary active euthanasia (VAE) and physician-assisted suicide (PAS) as part of palliative care. Japan stands out as the most aged country in the developed world, and while the need for palliative care for older adults with dementia has been noted, there has been reluctance to openly address VAE and PAS. Methods We conducted an online questionnaire survey using a vignette case to investigate the attitudes of Japanese physicians and the general public towards VAE and PAS, and the factors influencing these attitudes. Results The findings revealed that Japanese physicians did not display support for euthanasia (2%) and assisted suicide (1%); however, the general public supported euthanasia (33%) and assisted suicide (34%). Notably, among the general public, males exhibited significantly higher support for PAS than females. Conclusion Japanese physicians and the general public expressed a more negative stance towards VAE and PAS compared with their counterparts in Western countries. This disparity may be attributed to the influence of the Buddhist view of life and death and family-centeredness in the Japanese culture, which affects people’s attitudes towards assisted dying. The gap between physicians and the general public could potentially lead to challenges in medical practice, thereby, necessitating the need for open discussions in the future.